Automated external defibrillator (AED) use among paramedics in the Emergency Department – what are the obstacles in using the automated external defibrillator in the pre-hospital care settings? - Mohd Khairi AL; Nik Azlan Nik Muhamad; Faizal Amri H (Pusat Perubatan Universiti Kebangsaan Malaysia, 2018)
This study determined factors that influence usage of automated external defibrillation (AED) on out-of-hospital cardiac arrest among paramedics in Emergency Department of Universiti Kebangsaan Malaysia Medical Centre (UKMMC). It was a cross sectional prospective study conducted between December 2013 and January 2014. Paramedics from Emergency Department were enrolled and assessed using the self-filled questionnaire consisting of multiple sections including knowledge assessment, training and practice. In total, 53 paramedics participated in this study. Only 62% participants used AEDs previously. Not more than 83% participants admitted that they would use it if required. A positive correlation was observed between age and work experience with knowledge on AED usage (p=0.001 and p=0.005, respectively). Government’s institute graduates possess better knowledge and higher confidence level than private institutions graduates (p<0.001). Positive correlation existed between working experience and confidence level in deciding to use (p=0.006), application (p=0.019) and troubleshooting in regards of AED use (p=0.002). The main factor for low confidence level of AED use was lack of training (73.6%) which resulted in reduced confidence to initiate use (45.3%). Eighty eight percent agreed that training is essential before any AED use. Forty one percent felt that Malaysian public is not ready for AEDs use. As a conclusion, AED usage and knowledge among paramedics is still poor and further training is crucial for the improvement of pre-hospital care in Malaysia.